2004
DOI: 10.3130/jaabe.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Natural Ventilation Airflow Rates from Single-sided Heated Solar Chimney for Buildings

Abstract: Heat transfer process and natural ventilation driven by a solar chimney attached to a sidewall of building are investigated with CFD technique (MITFLOW) in detail. In this paper, conditions and parameters studied in the modelling study are the cavity width of the solar chimney, the wall temperature, the height and breadth of the solar chimney, the ratio of outlet area to inlet area as well as the outlet location of the solar chimney. The ranges of calculation parameters focused on a solar chimney with single-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…The cavity width of 0.2 m was chosen as most of previous studies suggested on that size as the effective width [27e29]. Meanwhile, the ratio of 1:10 (cavity width:height) is suggested by Bouchair [27] and Li et al [30] for the vertical solar induced ventilation configuration, namely solar chimney and Trombe wall.…”
Section: The Developed Prototype Devicementioning
confidence: 99%
“…The cavity width of 0.2 m was chosen as most of previous studies suggested on that size as the effective width [27e29]. Meanwhile, the ratio of 1:10 (cavity width:height) is suggested by Bouchair [27] and Li et al [30] for the vertical solar induced ventilation configuration, namely solar chimney and Trombe wall.…”
Section: The Developed Prototype Devicementioning
confidence: 99%
“…The effect of the slope on the flow out of the stack was studied by authors in [15], which showed that the absorption is optimal, for an angle of inclination varying between 40° and 60°. The processes of heat transfer and efficiency of natural ventilation driven by a solar chimney have been studied in [16]. Authors in [17] published a review of the main characteristics of chimney solar power plants.…”
Section: Imentioning
confidence: 99%
“…Hirunlabh et al( 1999). Li, et al (2004),investigated heat transfer process and natural ventilation driven by a solar chimney attached to a sidewall of building ,with CFD technique in detail. They studied the chimney cavity width, wall temperature, height and breadth, the ratio of outlet area to inlet area as well as the outlet location of the solar chimney.…”
Section: Introductionmentioning
confidence: 99%